2008
DOI: 10.1016/j.ijsolstr.2007.12.008
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale continuum model of the grain-size dependence of the stress hysteresis in shape memory alloy polycrystals

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(70 citation statements)
references
References 60 publications
2
67
1
Order By: Relevance
“…[8]. Note that an inverse relationship is observed in nano-crystalline materials [16], however, this effect is not covered by the present study.…”
Section: Minimization Of Total Incremental Energy Supplycontrasting
confidence: 58%
“…[8]. Note that an inverse relationship is observed in nano-crystalline materials [16], however, this effect is not covered by the present study.…”
Section: Minimization Of Total Incremental Energy Supplycontrasting
confidence: 58%
“…3-6 It has been reported that the H of the nanostructured polycrystalline NiTi SMA is very sensitive to the GS 7,8 and that the thermally-induced martensitic PT can be completely suppressed when the GS falls below 60 nm. 9 In many applications, H and dr=dT are the most important properties 10,11 and design parameters of the SMA device and structures.…”
Section: 2mentioning
confidence: 99%
“…4). 22 For the stress-induced PT process in polycrystalline NiTi, it has been shown that 7,23 the hysteresis originates from the nucleation of martensite in individual grains as the result of numerous microscopic instability of the system. To illustrate the GS effect on hysteresis (dissipation) in the simplest way, we consider the specific Helmholtz free energy change DW of a single one-dimensional cylindrical grain before and after PT under external stretching as shown in Fig.…”
Section: 2mentioning
confidence: 99%
“…Simulation of martensitic phase transformation in SMAs such as NiTi is computationally challenging due to the intricate stochasticity associated with the formation of different martensite phases (different martensite variants) occurring over a hierarchy of spatiotemporal scales [11,12]. The developed mechanisms in terms of internal strain or energy associated with the phase transformation from the parent austenite phase to the various martensite variants varies with the variants, thus, quantification of all different phase transformation mechanisms requires a large number of computationally burdensome fine scale simulations.…”
Section: Introductionmentioning
confidence: 99%